Definição de regimes de desbastes e poda economicamente ótimos para Pinus taeda - Acerbi Júnior, Fausto Weimar (1998)
This study had the objectives of simulating and evaluating, on the economic point of view, thinning regimes for Pinus taeda for obtaining the multiproducts from the wood and simulating and evaluating thinning regimes and pruning to obtain the clearwood and wood for multiple uses. The area of study, belonging to the enterprise PISA FLORESTAL S.A., is located in the county of Jaguariaiva, state of Paraná - Brazil. The first chapter deals with tests of 3 scenarios with different numbers, time and thinning intensities from different initial planting densities at different levels of productivity. The management regimes were submitted, in the investment analysis, to 3 discount rates, for plantings on level and rough lands, as well as, on rented and owned lands, totaling 133,920 different management options. The growth and yield values were obtained and thinning simulations were made by the PISAPRO software. The economic analyses were performed through the maximization of the present general net value by using the INVEST software. The management regimes, which presented the highest profitability for the class I site, specified production costs and prices, were those with planting of 1667 trees per hectare, and final cutting at 21 or 22 years after 2 thinning operations: the first one at 12 years maintaining 800 trees/ha and second one at 14 years maintaining 400 to 600 trees/ha. For the site II, the best option was the adoption of management regimes with planting 1667 trees/ha, and final cutting at 22 years after 2 thinning operations: the first one at 12 years of age maintaining 800 to 900 trees/ha and second one at 14 years maintaining 400 trees/ha. For the site III, the best option was the adoption of management regimes with planting 1333 trees/ha, and final cutting at 22 years after 2 thinning operations: the first one at 12 years of age maintaining 800 to 900 trees/ha and second one at 14 years maintaining 400 to 500 trees/ha. For the sites IV and V, there was no profit for any combination tested (management regimes). In the second chapter, 2 scenarios were tested with different numbers, time and thinning intensities from different initial planting densities, at different levels of productivity, aiming at the production of pruning wood, clearwood and no pruned wood for several uses. The generated management regimes were submitted, during the investment analysis, to 3 discount rates for plantings on both plain and rough lands, on rented and owned lands and for 6 different options of pruned wood prices related to no pruned wood, totaling 344,088 different management options. For obtaining clearwood, necessarily a pre-commercial thinning (first thinning) must be done at the young ages (4 to 5 years) followed by pruning. The management regimes, which presented highest profitability for class I and II sites, were those with 833 trees per hectare initially, and with final felling at 21 years after 3 thinning operations: a pre-commercial thinning followed by pruning at the age of 4 maintaining 500 trees/ha, a commercial thinning at the age of 12 maintaining 400 trees/ha and a third thinning (commercial) at 14 maintaining 100 trees/ha. For the site III, the best option was the adoption of management regimes with 1111 planted trees/ha and final cutting at 20 years, after the accomplishment of a pre-commercial thinning followed by pruning at the age of 4 maintaining 500 trees/ha and a commercial thinning at the age of 12 maintaining 200 trees/ha. The second pruning for the 3 classes of the site was achieved between 7 and 8 years of age.